-2(-4 + 3c) – 2c
I'd like to give you some understanding of what the property is and why we use it.
First, think of a simple example. 3 x 7 = 21. But 7 can be decomposed into 2 + 5 so
3 x 7 = 3 x (2 + 5) = 21
In order for the equation to remain true, we have to be able to distribute the 3, or give him to each number in the parenthesis.
3 x (2 + 5) = 3 x 2 + 3 x 5 = 6 + 15 = 21.
When you're trying to understand something in math, always use a simple example to help you work through the concept.
Now, for your problem, you have
-2(-4 + 3c) – 2c = -2 x -4 + (-2)x3c - 2c
-2(-4 + 3c) – 2c = 8 - 6c - 2c
There are two kinds of terms here, numbers with c and numbers without a c. You can combine the numbers with a c. Think of it like this, the two terms with c have had a c distributed to them. So, we can factor out, or reverse distribute, the c
-2(-4 + 3c) – 2c = 8 + c(-6 - 2) = 8 - 8c
But now, look at what we have, the two terms each have an 8 so we can reverse distribute the 8
-2(-4 + 3c) – 2c = 8(1 - c)
So factoring and distribution go hand in hand in our calculations! We call these inverse processes and if you have a good grasp on them, then your algebraic calculations will go more smoothly!
Hello Manosh. The first step in this problem is to multiply everything inside the parenthesis by -2.
(-2) x (-4) + (-2) x (3c) - 2c Which simplifies to...
8 - 6c - 2c Then, simplify like terms.
8 - 8c Which can also be simplified by pulling the common factor of 8 out in front to make...
8(1 - c) And that's it. I hope that helps!
-2(-4 + 3c) – 2c
= -2(-4) - 2(3c) - 2c, distributive property
= 8 - 6c - 2c
= 8 - 8c <==Answer